Variants of the ABCA3 gene might contribute to susceptibility to interstitial lung diseases in the Chinese population - Zhou, Wei (Sci Rep, 2017)
ATP-binding cassette A3 (ABCA3) is a phospholipid carrier that is mainly expressed in the alveolar epithelium. Biallelic mutations of ABCA3 has been associated with fatal respiratory distress syndrome and interstitial lung disease (ILD) in children. However, whether variations in ABCA3 have a role in the development of adult ILD, including idiopathic pulmonary fibrosis (IPF), remains to be addressed. In this study, we screened for germline variants of ABCA3 by exons-sequencing in 30 patients with sporadic IPF and in 30 matched healthy controls. Eleven missense variants, predominantly in heterozygous, were found in 13 of these patients, but only two missenses in 2 healthy controls. We then selected four of the detected missense variants (p.L39V, p.S828F, p.V968M and p.G1205R) to performed cohort analysis in 1,024 ILD patients, containing 250 IPF and 774 connective tissue disease-ILD (CTD-ILD) patients, and 1,054 healthy individuals. Our results showed that the allele frequency of p.G1205R, but not p.L39V, was significantly higher in ILD patients than in healthy controls. However, no additional subject carrying the variant p.S828F or p.V968M was detected in the cohort analysis. These results indicate that the heterozygous ABCA3 gene variants may contribute to susceptibility to diseases in the Chinese population.